Labor Contestation at Walmart Brazil Limits of Global Diffusion in Latin America - Martin, Scott B.; Veiga, João Paulo Cândia; Galhera, Katiuscia Moreno (Governance, Development, and Social Inclusion in Latin America, 2021)
XXVII, 309 p. 4 illus.